Implementasi Framework Laravel Dalam Perancangan Sistem Informasi Penjualan UKM Kota Surakarta - Yuli Siyamto; Joko Triyanto; Muhammad Rafi Alwatoni (LPPM Universitas Putera Batam, 2023)
Small bussiness in Surakarta still use conventional sales process transactions. The disadvantages of conventional transactions are the slow transaction process and long report generation. The aim of this research is to build a complete sales information system, to provide product information, transactions and report accuracy. This makes it easier for their business. The method implemented to build this system is the Waterfall method. The results of this research are in the form of a website-based sales information system. The system has been tested using the black box testing method and resulted in the system running well and according to its function.